Perceiving One’s Own Limb Movements with Conflicting Sensory Feedback: The Role of Mode of Movement Control and Age - Wang, Lei; Sutter, Christine; Dangel, Ronald J.; Musseler, Jochen; Disselhorst-Klug, Catherine (Frontiers in Psychology, 2012)
Previous studies have demonstrated a great uncertainty in evaluating one's own voluntary actions when visual feedback is suspended. We now compare these limitations in younger and older adults during active or passive limb movements. Participants put their dominant hand on a robot arm and performed movements actively or the relaxed limb was moved passively. Either a distorted visual feedback or no visual feedback at all was provided during the movement. Perception of limb movements was attenuated through visual feedback. This effect was more pronounced in older adults. However, no difference between active and passive movements was found. The results provide evidence for the limited awareness of body effects, even in the absence of voluntary actions.